Hip arthroscopy for the treatment of osteoid osteoma of the acetabulum: a case report study - Calanna, Filippo; Maione, Alessio; Fioruzzi, Alberto; Randelli, Filippo (Acta Biomedica Atenei Parmensis, 2021)
Osteoid osteoma (OO) of the acetabulum is a quite rare pathology, with an overall incidence of 0,5%. Frequently the diagnosis of OO may not be simple to obtain, because the clinical presentation can mimic other common hip pathologies. We present a case report of OO of the anterior/superior edge of the acetabular fossa associated with a degenerative lesion of the acetabular labrum and with a concomitant femoral neck cam. The patient was refractory to prior pharmacological therapy with NSAIDs so arthroscopic treatment was performed. As a rational strategy, we trimmed the region of the tumor and we finally excised the nidus of the OO. Finally a femoroplasty and a partial labrectomy were performed. At the last follow-up the patient was symptom-free and able to walk with full weight bearing. The nocturnal pain was gone and his ROM improved fully without pain. The arthroscopic procedure, being less invasive, represents a valid option in the treatment of OO, allowing to treat radically the tumor and concurrently diagnose and repair any chondral or soft tissue injuries.